ANALISIS KUALITAS E-GOVERNMENT PADA WEBSITE “SIAP OM” DI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN DEMAK - Hermadianti, Sajida; Hanani, Retna (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2025)
The SIAP OM website was designed to facilitate online population administration services by the Demak District Population and Civil Registration Office. However, its implementation still faces various obstacles. This study aims to analyze the quality of E-Government on the SIAP OM website based on the dimensions of efficiency, trust, reliability, and citizen support. This research uses the E-Govqual theory proposed by Papadomichelaki Mentzas which consists of the dimensions of efficiency, trust, reliability, and citizen support as research indicators and uses the Community Satisfaction Survey (SKM) method based on the Regulation of the Minister of Administrative Reform and Bureaucratic Reform Number 14 of 2017 concerning Guidelines for Preparing Community Satisfaction Surveys for Public Service Delivery Units as a method of calculating IKM. This research uses a descriptive quantitative approach, with data collected through questionnaires and interviews. The research population includes the people of Demak Regency who have accessed the SIAP OM website, with a sample size of 100 respondents. The questionnaire was distributed through social media Instagram and WhatsApp. The selection of sources was carried out by purposive sampling. The sources of this research are the Secretary of Dindukcapil Demak Regency and users of the SIAP OM website. In analyzing the data using the Community Satisfaction Survey calculation and calculated using Microsoft Excel. The results showed that the overall service quality of the SIAP OM website is still classified as “D” or “Not Good” with an IKM score of 63.41, characterized by low efficiency, trust, reliability, and community support in using e-government services.